THE IMPORTANCE OF FREE ECONOMIC ZONES IN ECONOMIC DEVELOPMENT - Nozimov Eldor Anvarovich (PT. Antis International Publisher, 2024)
General Background: Free Economic Zones (FEZs), including Special Economic Zones (SEZs), are established worldwide as strategic initiatives to foster economic development, promote innovation, and attract foreign direct investment (FDI). These zones, typically positioned near key transportation hubs, are distinguished by unique incentives such as tax reductions and regulatory leniency, enhancing their appeal to global enterprises. Specific Background: Over time, SEZs have evolved from traditional trade hubs into sophisticated economic spaces integrating modern technology, sustainable practices, and diverse business models. Despite their recognized benefits, the challenges SEZs face, such as regulatory loopholes, environmental impact, and potential socioeconomic inequality, have yet to be fully understood in terms of their broader implications for sustainable economic growth. Knowledge Gap: While substantial literature discusses the general economic advantages of SEZs, there is limited analysis on balancing these benefits with regulatory and ethical considerations essential for sustainable development. Aims: This study aims to comprehensively examine the role of SEZs in global trade and economic integration, emphasizing their economic advantages while identifying and addressing the inherent risks. Results: Using a descriptive and analytical methodology, this study highlights SEZs’ capacity to attract FDI, stimulate job creation, and foster exports. The findings underscore the complex dynamics within SEZs, identifying key regulatory, environmental, and social challenges that must be addressed to sustain their positive economic impact. Novelty: This research offers a holistic evaluation of SEZs, proposing balanced policy recommendations to bridge economic gains with sustainable and equitable growth. Implications: The findings suggest that the success of SEZs will increasingly rely on adaptive policy frameworks that mitigate risks while maintaining their economic viability. Policymakers and stakeholders are encouraged to prioritize regulatory strength, environmental responsibility, and social equity to ensure SEZs’ role as sustainable engines of economic advancement.